Dermoscopy of piloleiomyoma - Joanna Pogorzelska-Dyrbuś; Jacek Pająk (Termedia Publishing House, 2021)
Piloleiomyomas occur rarely and the literature regarding their dermoscopy is scarce. These tumours most commonly present as multiple nodules located on the trunk or the head. The diagnostic difficulties may be caused by their solitary appearance. Therefore, dermoscopy can serve as a non-invasive and accessible diagnostic modality to distinguish leiomyomas from other solitary tumours. This report presents the dermoscopy image of a piloleiomyoma developing on the trunk in a 35-year-old man. A yellowish homogenous background with the presence of delicate network and arborizing telangiectasias on the periphery were present, along with hypopigmented areas. The dermoscopy image of the lesion was characteristic for piloleiomyoma. Unusuall was the abundance of vessels, what is infrequent in this type of tumours.